THE PROCEDURE FOR RESOLVING INVESTMENT DISPUTES IN INTERNATIONAL PROCEDURAL LAW - Nurmukhammedova Farrukha Fakhriddin Qizi (Scholar Express Journals, 2021)
Through this article, the procedure for resolving investment disputes in international procedural law, the concept of an investment dispute, the causes of an investment dispute, the principles of international law, international public law and private international law, the participation of subjects of international law in investment disputes, BIT, multilateral agreements were highlighted , the procedure for applying to the ICSID (hereinafter “ICSID” or “Center”) of the parties for the resolution of the investment dispute, consideration and execution of the case, also Allowing investment dispute to ICSID in the participation of the Republic of Uzbekistan, the problems of conformity of national laws to the norms of international law.
Keywords: Concept investment; investment dispute; international treaties; convention